2019
DOI: 10.1038/s41598-019-41779-w
|View full text |Cite
|
Sign up to set email alerts
|

Innervation is higher above Bone Remodeling Surfaces and in Cortical Pores in Human Bone: Lessons from patients with primary hyperparathyroidism

Abstract: Mounting evidence from animal studies suggests a role of the nervous system in bone physiology. However, little is known about the nerve fiber localization to human bone compartments and bone surface events. This study reveals the density and distribution of nerves in human bone and the association of nerve profiles to bone remodeling events and vascular structures in iliac crest biopsies isolated from patients diagnosed with primary hyperparathyroidism (PHPT). Bone sections were sequentially double-immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 75 publications
1
58
1
Order By: Relevance
“…Nonetheless, innervation of bone is most dense in the periosteum and marrow spaces, with relatively few nerves present in the mineralized bone ( 9 , 10 ). Furthermore, innervation density is increased at sites nearest to active bone remodeling surfaces ( 20 ).…”
Section: Skeletal Innervationmentioning
confidence: 99%
“…Nonetheless, innervation of bone is most dense in the periosteum and marrow spaces, with relatively few nerves present in the mineralized bone ( 9 , 10 ). Furthermore, innervation density is increased at sites nearest to active bone remodeling surfaces ( 20 ).…”
Section: Skeletal Innervationmentioning
confidence: 99%
“…In support of a clear association of nerves with bone metabolism, a recent study reported the presence of higher innervation density at the surface of bone remodeling in the iliac crest from patients with hyperparathyroidism. [198] The study further shows the distribution of both sympathetic and nonsympathetic nerves in bone and a higher innervation density present in the intracortical cavities compared to periosteum and bone marrow.…”
Section: Nerve Growth Factormentioning
confidence: 66%
“…[ 351,352 ] Much of bone's innervation is centripetally distributed, derived from periosteal fibers that branch within the compact bone and bone marrow. [ 19,353–355 ]…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…They are distributed throughout the skeletal tissues, including the periosteum and bone marrow. [ 19–21 ] Bone is richly innervated by peripheral sensory and motor nerves, which transport different excitation signals and covey information to the targeted cells or tissues. [ 22,23 ] Unlike vascularization, the process of nerve repair in bone defects is obscure, with no visibly‐discernible influence on short‐term healing.…”
Section: Introductionmentioning
confidence: 99%